The Haskins Society journal, Volume 24, 2012 studies in medieval history - North, William L.; Gathagan, Laura (Boydell & Brewer, 2013)
This volume of the Haskins Society Journal furthers the Society's commitment to historical and interdisciplinary research on the early and central Middle Ages, focusing on the Anglo-Saxon, Anglo-Norman, and Angevin worlds. The topics of the essays range from the complexities of landholding and service in England after the Norman Conquest and the place of Portugal in the legal renaissance of the twelfth century, to the purpose and audiences of copies of Anglo-Saxon charters produced by the late medieval community at Bury St Edmunds. There is an investigation of the hitherto overlooked narrative role of material objects in Orderic Vitalis' History, continuing the Journal's investigation of source-specific analyses, together with an exploration of the date and reliability of an important, but neglected, witness to the Norman conquest of Sicily. Other essays look at the longue durée of the ascetic practice of self-flagellation and its emergence in eleventh-century Italy; the place and meaning of religious practices in crusading, using the De expugnatione Lyxbonensi as laboratory; and aural and visual experience in the life and musical opus of Godric of Finchale. Contributors: Howard B. Clarke, Sarah Foot, John Howe, Monika Otter, Daniel Roach, Charles D. Stanton, Susanna A. Throop, André Vitória